Peritumoral Edema Relative to Meningioma Size Predicts Functional Outcomes after Resection in Older Patients. Issue 3 (22nd May 2018) - Loewenstern, Joshua; Aggarwal, Amit; Pain, Margaret; Barthélemy, Ernest; Costa, Anthony; Bederson, Joshua; Shrivastava, Raj K
Abstract: BACKGROUND: Resection of meningiomas in older adults is associated with increased complications and postoperative functional deficits. Extent of peritumoral edema (PTE), which has been associated with surgical prognosis, may represent a preoperative risk marker for poorer outcomes in older adults. OBJECTIVE: To quantitatively evaluate the relationship between preoperative PTE and postresection outcomes in older meningioma patients. METHODS: One hundred twelve older meningioma patients (age ≥ 60) with evidence of PTE on MRI were reviewed. Extent of PTE, measured as a ratio of edema to tumor volume (edema index, EI) using semiautomatic image-processing software, was correlated with postresection outcomes. Other preoperative factors were included as covariates in multivariate analyses. Results were compared to matched nonedema older patients. Receiver operating characteristic (ROC) curve analysis was performed to identify cut-off EI values to predict postoperative outcomes. RESULTS: EI was associated with functional decline (as measured by Karnofsky Performance Status, KPS) at 6 mo, 1, 2 yr, and most recent follow-up ( P s < .05), but not among the nonedema matched patients. Seizure or prior stroke additionally trended towards increasing the likelihood of lower KPS at 2 yr (odds ratio = 3.06) and last follow-up (odds ratio = 5.55), respectively. ROC curve analysis found optimal cut-off values for EI ranging from 2.01 to 3.37 to predict lower KPS at each follow-up interval. Sensitivities ranged from 60% to 80%, specificities from 78% to 89%, and positive and negative predictive values from 38% to 58% and 80% to 97%. CONCLUSION: Preoperative PTE may represent a significant marker of poor functional outcome risk in older adults and provides a quantitative measurement to incorporate into surgical decision-making.